REPRESENTATIVE COLLEGE PROGRAMS. - Littleton, A. C. (The Accounting Review, 1944)
Abstract In three recent issues of the periodical "Accounting Reviews" dated October, 1943, January and July, 1944, representative educational programs of accounting majors have been printed for sixty colleges in the U.S. and for two in Canada. It is the purpose of this article to analyse the data thus collected. The first analysis, will deal with the quantitative aspects of the programs. This will classify the courses according to the usual departments of instruction and thus indicate the fields of education which receive particular attention in most programs in the sample. A subsequent analysis will deal with course names in order to derive further indications of the educational pattern of college students who major in accounting. Public accountants and others who give employment to college graduates with a major in accounting may find these representative programs helpful. They are individual programs, each representing the work of an actual student who was graduated from the school named. They can be studied individually as one deals in the office with one man at a time.